Rolling contact fatigue resistance of Carbidic Austempered Ductile Iron (CADI) - Pedro, Diego Iván (2019)
The austempered ductile iron (ADI) with carbides in its microstructure, commonly known as CADI, is a relatively new variant of ductile iron intended to resist abrasive wear in different tribosystems by selecting the appropriate casting procedure, chemical composition and heat treatment. In this case, the rolling contact fatigue (RCF) behavior of CADI with two heat treatments was compared to that of ADI to evaluate its potential use as an alternative material for machine parts subjected to point or line rolling/sliding contact fatigue conditions. The RCF tests were done in a flat washer type testing machine under contact conditions (load, roughness, lubricant and velocity) leading to contact of micro-asperities. When compared to ADI, the microstructure of CADI has similar nodularity and nodule size, but the nodule count is lower because part of the carbon is combined in the form of carbides. While having similar hardness and failure appearance, CADI RCF resistance was higher than that of ADI. It was observed that the nodules at or near the surface work as crack nucleation sites and then, when replacing part of the graphite content with carbides the load carrying capacity and the RCF resistance are improved with respect to those of ADI.